(untitled) (World Bulletin of Management and Law, 2025)
This article analyzes the regulatory legal documents adopted in recent years within the framework of reforms carried out in the field of ensuring public order and safety by the internal affairs bodies. It highlights their role as a legal foundation for maintaining public order and security, the essence of the social relations regulated by these legal norms, and the prospects in this direction. The article also presents conclusions based on the analysis of scientific research and legal literature concerning the topic.